Biological Aspects of Diopatra claparedii Grube, 1878 (Onuphidae, Polychaeta) Maintained at Different Salinity Levels - Wibowo, Eko Setio; Atang, Atang; Setiyono, Eko; Hana, Hana; Simanjuntak, Sorta Basar Ida; Susilo, Untung; Sucharitakul, Phuping; Apriyanti, Yuni; Pamungkas, Joko (Marine Science Department Diponegoro University, 2025)
Diopatra claparedii Grube, 1878, is a tubicolous polychaete species widely used as fishing bait by local anglers in Cilacap, Central Java, Indonesia. Little is known about its biological characteristics despite its ecological and economic importance. This study aimed to examine the survival rate, growth, metabolic rate, and osmoregulatory capacity of D. claparedii under different salinity conditions. The experiment was conducted using plastic containers (20 × 30 × 25 cm) filled with a muddy substrate and water at four salinity levels: 10, 15, 20, and 25 ppt, with each treatment replicated five times. The results showed that the survival rate of D. claparedii ranged from 87% to 93%, while its growth varied between 0.17 and 0.58 g. The metabolic rate, measured in terms of oxygen consumption, ranged from 0.201 to 0.467 mg·g-¹·h-¹. The osmoregulatory capacity of the worms varied between 1.26 and 1.54 mOsm·kg-¹ solvent. Statistical analysis indicated that salinity did not significantly affect survival (p> 0.05). However, it significantly influenced growth, metabolic rate, and osmoregulatory capacity (p< 0.05). The results suggested that a 15–25 ppt salinity range was more favorable for the species, with 20 ppt being the most optimal level for its maintenance and growth. This study highlights the potential for cultivating D. claparedii under controlled conditions, providing a sustainable alternative to wild harvesting. As polychaete farming has been successfully implemented in several countries, similar efforts could be applied in Indonesia to support local fisheries while conserving natural populations.